An Investigation of Situational Inhibitors to Informal Learning amongst Accountants - Wahab, Muhammad Syahir Abdul; Saad, Ram Al-Jaffri; Samsudin, Mohammed Amir Mat (International Journal of Economics and Financial Issues, 2016)
A case study was conducted to investigate situational inhibitors to informal learning activities amongst accountants in a public firm in Malaysia. Four situational inhibitors emerged from the data analysis. The accountants reported that lack of time, lack of proximity to colleagues' working areas, lack of support from others and structural inhibitor as the inhibitors to the learning. The paper proceeds to outline the theoretical and practical implications as well as suggestions for future research. Keywords: Accountant, Informal Learning, Situational Inhibitors JEL Classification: D9